A barrister’s role in the plea decision: an analysis of drivers affecting advice in the crown court - Barry, James Dominic Edward (2010)
PhDThis thesis explores the reasons behind barristers' advice to defendants in the Crown Court on plea, primarily through interviews with criminal law practitioners themselves. Beginning with a critical overview of the current research, the thesis argues that the views of criminal barristers are a neglected significant source of information in developing an understanding of why particular advice is given. The thesis, in the context of other research, analyses the data from interviews conducted with current practitioners on the London and the Midlands Circuits, and discusses the various drivers that act upon barristers in deciding what advice to give. Starting with the actual advice given and the advising styles adopted, the thesis explores why guilty pleas might be advised and plea bargains sought with prosecutors. The research goes on to examine the impact of various influences, including legal, ethical, cultural, regional and financial to produce an overview of what factors impact upon a barrister's advice. The thesis argues that the current view of the Bar sustained in much of the literature is insufficiently nuanced and outdated, and that the reasons behind the advice given to defendants on plea are extraordinarily varied, occasionally contradictory, and highly complex. The thesis concludes that the data from the interviews warrants a rethink of why particular advice is given and that discovering what drives barristers’ advice is critical to formulating law and government policy